(untitled) (Research, Society and Development, 2021)
Introduction: Currently, the occurrence of type 2 Diabetes Mellitus (DM2) is increasing gradually, which becomes a global concern. This concern is due to the fact that some studies suggest that diabetes is associated with an increased risk of developing severe forms of COVID-19. Objective: To conduct a systematic review of DM in relation to COVID-19. Methodology: This is a systematic literature review study using the PubMed (United States National Library of Medicine) and Science Direct databases with the descriptors “Diabetes mellitus”, “covid-19”, “risk factors / Diabetes mellitus”, “ covid-19 ”,“ comorbidity ”. The search was limited based on publication date (5 years’ time: 2016-2021), species (humans), available languages (English, Spanish and Portuguese). Articles that were not part of the COVID-19 x Diabetes Mellitus theme were excluded from the research. Results and Discussion: During the study, it was possible to observe the strong correlation between the poor prognosis of COVID-19 and Diabetes type 1 and 2. Since diabetes immunocompromises the human body, it is understood that an infection secondary to COVID - 19 is more persistent and lethal. Conclusion: It is concluded that patients with diabetes who contract have a worse prognosis when compared to non-diabetic patients. These patients should receive greater attention from the health system, receiving preventive measures such as strict glycemic control. It is also urgent to show this population the importance of vaccination.